A guidewire introducer as a ureteral foreign body: A case report - Sener, Tarik Emre; Cloutier, Jonathan; Audouin, Marie; Villa, Luca; Traxer, Olivier (Canadian Urological Association Journal, 2015)
A 63-year-old male, previously treated for a ureteral tumour by a right-sided segmental ureterectomy and end-to-end anastomosis of ureteral segments, was referred to our clinic for endoscopic follow-up. During his follow-up, he was diagnosed with partial right-sided ureteral stricture which eventually progressed to complete obstruction. During the ureteroscopy, as the stenotic segment did not allow passage of an hydrophilic guidewire, an antegraderetrograde approach was decided. On the antegrade endoscopic view, a near-complete stenosis was diagnosed and a nephrostomy catheter (12 Fr) was placed. A second intervention was planned and from the nephrostomy tract, the ureteroscope was placed into the right pyelocaliceal system. The diagnostic ureteroscopy revealed a foreign object proximal to the stenotic area. Right-sided segmental ureterectomy of the stenotic segment with ureteroneocystostomy and removal of the foreign object was performed. This is the only case in literature to reveal a guidewire introducer as a ureteral foreign body. This case also highlights the importance of the fragility of the ureter, the importance of the equipment, of always being watchful during a surgery, and the importance of checking the integrity of the equipment at the end of each procedure.